8B and hep solar neutrino detection by terrestrial experiments - Karathanou, G. I.; Tsikoudi, V. S.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
Solar neutrino spectra of 8B and hep neutrinos produced by pp-chain reactions are analysed for various nuclear detectors in current terrestrial experiments. The well known folding method is applied by employing appropriately simulated solar neutrino distributions and using recently calculated total cross section of neutrino- nucleus processes. We focus on the nuclear target of current experiments like MOON and ICARUS as well to other promising nuclear isotopes.